A Study of Impoliteness Strategies in Daily Conversation at SMA Muhammadiyah Rambah - Sari, Novita; Eripuddin, Eripuddin; Rasyidah, Ummi (Science, Technology and Education Care (STEDCA), 2025)
This study aims to determine the expressions of impoliteness spoken by students in classroom interactions based on the Strategies of Impoliteness at Muhammadiyah Rambah High School. Researchers have studied five Strategies of Impoliteness: Bald on Record Impoliteness, Positive Impoliteness, Negative Impoliteness, Sarcasm or Mock Impoliteness, and Withhold Impoliteness type. This research is descriptive qualitative, where the data source is in the form of field notes recorded by researchers when conducting research and audio and video recordings during student interaction in class. In this research, the researcher researched two eleventh-graders majoring in science. In the results, researchers found that some students tend to say sentences or use inappropriate words when uttered by a student in class; as for what makes students say the utterance, it is because students are used to saying the sentence or phrase that is not polite in everyday life. From the study results, the researchers also concluded that some students utter impolite speech to get the attention of their friends or the teacher and relieve their boredom when studying in class.